The Effects of Information Asymmetry, Earning Management, Voluntary Disclosure and Market Value of Equity on Cost of Equity Capital - Rizki Istiawati Sunaryo; Dian Saripujiana (Universitas Hayam Wuruk Perbanas, 2018)
This study aims to examine the effect and prove that (1) the higher of the information asymmetry, the higher of the cost of equity capital, (2) the higher of the earning management caused the higher of the cost of equity capital, (3) the higher of the voluntary disclosure caused the lower of the cost of equity capital and (4) the higher of the market value of equity caused the lower of the cost of equity capital. This research was conducted in the manufacturing companies sector listed on Indonesian Stock Exchange (IDX) in 2012-2014. This study used a purposive sampling method for getting sample. The data were analyzed using Multiple Linear Regression Analysis with one-tailed test with SPSS 22.0 program. The results show that market value of equity were statistically supported or hypothesis accepted. While the information asymmetry, earning management and voluntary disclosure were not statistically supported, although the information asymmetry had a significant effect but the hypothesized results were different so the hypothesis remains rejected.